Coconut Biotechnology - Kong, Eveline Y.Y.; Mu, ZhiHua; Vidhanaarachchi, Vijitha R. M.; Nguyen, Quang Thien; Sisunandar, Sisunandar; Kalaipandian, Sundaravelpandian; Panis, Bartholomeus (2024)
Coconut is a valuable industrial crop that has a multitude of uses and applications, such as in the production of copra, various foods and drinks, soaps and detergents, furniture and household goods, and bulk materials for manufacturing, medicines and cosmetics. A wide range of biotechnology approaches are available to bring advancements in coconut propagation, conservation, crop improvement, and tolerance to pests and diseases. Many have been accomplished with great success, while others still require further optimization prior to commercial application. This chapter provides a summary of these advancements, in particular a history of the advancements in coconut tissue culture, as well as the challenges and opportunities of this technology.